Characteristics of Screen Mesh Wick Heat Pipe with Nano-fluid as Passive Cooling System - W.N. Septiadi; N. Putra; M. Juarsa; I.P.A Putra; R. Sahmura (Atom Indonesia, 2013)
The heat pipe is one of the cooling media which is potential to be developed for the passive cooling system for nuclear reactors. To enhance the performance of the heat pipe, nanofluids have been used as the working fluid for the heat pipe. This paper studies the characteristics of nanofluids as the working fluid of heat pipe with screen mesh wick, which was the mixture of nano-sized particles (Al2O3 and TiO2) with water as the base fluid. The nanoparticles have average diameter of 20 nm, made with 1% to 5% volume fraction. The heat pipe thermal performance was tested using heater with different heat load. The experimental result shows the use of 5% Al2O3-water improve the thermal performance by reducing the temperature at evaporator side as much as 23.7% and the use of TiO2-water reduce the temperature at evaporator side as much as 20.2% compared to the use of water. The use of nanofluid also decreases the thermal resistance of heat pipe. As the use of nanofluid improves thermal performance of heat pipe, it has a potential for applications along with heat pipes at nuclear reactors.Received: 04 December 2012, Revised: 13 February 2013, Accepted: 25 February 2013